2004
DOI: 10.1177/0954008304044104
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Ultraviolet Radiation in Sources of Hyperthermal Atomic Oxygen. Photodestruction of Polytetrafluoroethylene (PTFE) and Teflon FEP for hdication of this Radiation

Abstract: Most facilities for testing the stability of spacecraft materials under attack by fast atomic oxygen (AO) are based on the generation of hypersonic beams of AO in nozzle sources with the use of continuous electrical discharges or in laser pulse-induced breakdown of the gaseous oxygen. In both cases, the sources of fast AO are simultaneously quite intense sources of vacuum ultraviolet (VUV) radiation. In the present study the intensity of VUV radiation with wavelengths > 115 nm from fast AO source were direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…They found that, unlike the photolysis of PP and PE, CC bond generation is not a major process. They found CF n ( n = 1–3) in the ejecta, indicating that the polymer CC backbone undergoes scission, a process also observed by Skurat and Nikiforov 26. Ono et al estimated the quantum yield for atomic fluorine photolysis at 147 nm to be 0.0025.…”
Section: Introductionmentioning
confidence: 78%
“…They found that, unlike the photolysis of PP and PE, CC bond generation is not a major process. They found CF n ( n = 1–3) in the ejecta, indicating that the polymer CC backbone undergoes scission, a process also observed by Skurat and Nikiforov 26. Ono et al estimated the quantum yield for atomic fluorine photolysis at 147 nm to be 0.0025.…”
Section: Introductionmentioning
confidence: 78%
“…Extensive efforts have been undertaken in both space environments and ground-based test facilities in order to unravel the erosion mechanisms of FEP Teflon. [31][32][33][34][35][36][37][38][39][40][41] FEP Teflon has strong absorption bands at VUV wavelengths. VUV radiation breaks C-C and C-F bonds and creates fragments that become volatile.…”
Section: Combined Effects Of Atomic Oxygen and Ultraviolet Lightmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] When spacecrafts travel at the first cosmic velocity in LEO, the surface materials collide with AOs at velocities of 7-8 km s À1 , with translational energies of 4-5 eV and fluxes of 10 13 -10 15 atoms cm À2 s À1 , which causes serious erosion and degradation to spacecraft materials. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Yellow polyimides Kapton H or Kapton NH have been widely used in LEO, for their low density, thermal stability, flexibility, and durability to vacuum ultraviolet (UV). However, they suffer from strong oxidation under hyperthermal AO attack when operating in orbit, for their elements of carbon (C), hydrogen (H), O, and nitrogen (N) are easily oxidized by the high-velocity AO interaction, to form volatile gas molecules and leave surface, resulting in mass loss of materials.…”
Section: Introductionmentioning
confidence: 99%